A study of the cellular infiltrate of the proximal jejunal mucosa in ulcerative colitis and Crohn's disease. Issue 3 (March 1975) - Ferguson, R; Allan, R N; Cooke, W T
Abstract : The cellular infiltrate of the proximal jejunum has been compared between 20 subjects without gastrointestinal disease, 20 subjects with ulcerative colitis, and 26 subjects with Crohn's disease. A significant increase (P smaller than 0.001) in the plasma cell infiltrate was noted in subjects with ulcerative colitis and a more marked increase in subjects with Crohn's disease (P smaller than 0.001). Such increases may be relevant to raised serum IgA levels following panproctocolectomy for ulcerative colitis or recurrence in the small intestine in Crohn's disease.